Enhancing Health and Safety Practices in Construction Site in Developing Nations Through Technology Advancement in South Western Nigeria - Lawal, Mubaraq; Mahmud, Abba; Dere, Ismail Gbolahan; Owoicho, Thankgod Agbo (UI Scholars Hub, 2025)
The construction sector plays a critical role in urban development and economic growth, yet it continues to face major challenges that threaten worker health and safety. Traditional safety measures are not always sufficient for the complex conditions found on construction sites, which creates a need for technology‑based solutions. This study investigates the relationship between technology adoption and health and safety practices in the construction industry in Lagos, Nigeria. The study identifies the major causes of site accidents, examines the level of technology use on construction sites, and reviews existing literature through both primary and secondary data. Primary data were collected from registered construction professionals, while secondary data were obtained from journals and conference papers. Questionnaires were distributed through email and social media platforms, and 141 valid responses were received. Findings show that the leading causes of construction hazards were lack of training (mean = 3.79) and non‑compliance with safety procedures (mean = 3.70). The overall level of technology adoption for site safety was low (mean = 2.75), although some tools were more widely used than others. The most significant barrier to adoption was the high cost of acquiring new technologies (mean = 4.52). Statistical analysis showed a strong positive correlation between technology adoption and accident reduction (r = 0.62, p = 0.001). Technology‑based safety training was significantly associated with improved compliance (χ² = 12.45, p = 0.002). Wearable technology also had a significant effect on incident reporting (F = 4.76, p = 0.012), and access to mobile safety applications showed a positive correlation with risk reporting (r = 0.45, p = 0.045). Overall, the study concludes that technology contributes positively to construction health and safety in southwestern Nigeria. The study recommends increased investment in training, awareness programs, and financial support to encourage wider adoption of safety technologies.